Revitalisasi Sistem ATS: Integrasi Smart Relay dan Teknologi Otomatisasi Suhu. - Kiswantono, Agus; Rozak Fakhrudin Syah , Ahmad; Muhibudin A, M Anas (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2023)
This research delves into the intricacies of an Automatic Transfer Switch (ATS) system anchored on the Zelio SR2A101BD smart relay. The exploration primarily centers on the functionality and performance metrics of the system's components, notably the PZEM-004T sensor for electrical data acquisition and the DS18B20 for temperature sensing. Through meticulous experimentation and testing, the research underscores the system's capability to seamlessly transition between primary (PLN) and secondary (PLTS) power sources during interruptions or failures. Utilizing the Zelio Soft 2 software as an analytical tool, the research gauges the system's efficiency and responsiveness. Noteworthy findings highlight an average transition time of 4.39 seconds from PLN to PLTS and 1.06 seconds in the opposite direction. This research culminates in affirming the ATS system's reliability and its potential as a pivotal component in modern electrical infrastructures.